VERIFICATION OF SEVERAL IMPORTANT THEOREMS IN SIMPLE RANDOM SAMPLING USING R SOFTWARE - He, Chaobing (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2021)
This paper considers the verification of several important theorems in simple random sampling using R software. First several important theorems in simple random sampling are introduced systematically. Then computer program for the verification of these theorems is written using R. According to these R codes, the paper verifies these theorems. The output proves that the R codes are very practical and effective.